Advanced techniques in hybrid assembly of tunable lasers - Elsayed, Hossameldin (2024)
Semiconductor tunable lasers are employed in different applications due to their small size, low cost, and integrability. Their emissions span the spectrum from the visible range (400-700 nm) up to the mid-infrared range (2.5-10 µm). Hence, they are integral to different applications in the fields of communication, sensing, medicine, and spectroscopy. However, realizing high-performance integrated tunable lasers is very challenging. For example, the hybrid integration of different photonic devices usually suffers from misalignment, low coupling efficiency, and long-term instability. In this work, a hybrid integrated tunable laser high performance was demonstrated through UV-curable adhesive assembly. The study presents the usage of UV-curable adhesives and their role in realizing a robust and stable hybrid integration of GaSb-based reflective semiconductor optical amplifiers (RSOA) and Si3N4 photonic integrated circuits (PICs). It includes designing a semi-automated assembly process, conducting experiments to characterize the adhesives, and characterizing the hybrid laser. The assembled hybrid tunable laser achieved a maximum output power of 7.7 mW with a current threshold of 117 mA. In addition, wavelength emission at 1984 nm with tuning of 0.1 nm was demonstrated. These findings contribute to the advancement of reliable and efficient hybrid integration techniques for photonic devices.